Polio Vaccination Literacy Among Mothers of Selected Barangay Health Centers in a Component City - Vinco, Kristine Anne C.; Malaga, Xerxes G. (Technium BioChemMed, 2021)
Every health worker strikes hard for every child's death, most notably when it is due to a disease that is readily preventable with a safe and effective vaccine. The tragedy is hard to accept when health practitioners see the consequences of children missing out on vaccination first-hand. This research was intended to bridge the literature gap on the knowledge, and the reasons mothers comply with polio vaccination. The study was intended to assess the level of literacy on polio vaccination of mothers in selected barangays in Bago City when they are taken as a whole and grouped according to age, educational attainment, distance to health facility, number of children, family income, and barangay location administered. A descriptive-comparative research design using a very highly reliable and valid researcher made questionnaire was administered to respondents. The level of literacy of mothers on polio vaccination in selected barangays of Bago City when grouped according to age, educational attainment, the distance of health facility, number of children, family income, and barangay location was very high. The major reasons for compliance of mothers with polio vaccination can be attributed to health workers who can give follow up through home visits and any health professional who can give the polio vaccine. Due to reported vaccine scare and the current pandemic the study will benefit rural health administrators, community health nurses, and future researchers. Findings could provide rural health administrators with insights to conduct a re-assessment of the implementation of vaccination programs initiated by the Department of Health